The THE EFFECT OF BUDGET PREPARATION PARTICIPATION ON ORGANIZATIONAL PERFORMANCE WITH CLARITY OF BUDGET TARGETS AND JOB RELEVANT INFORMATION AS MEDIATION VARIABLES (Study of Seluma Regency Local Government): PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA ORGANISASI DENGAN KEJELASAN SASARAN ANGGARAN DAN JOB RELEVANT INFORMATION SEBAGAI VARIABEL MEDIASI (Studi Pada Pemda Kabupaten Seluma) - Khairiyah, Diah; Desi Fitria; Mardhiyah Dwi Ilhami; Riri Hermita Sari (Universitas Muhammadiyah Bengkulu, 2024)
The purpose of this study was to determine the effect of budgetary participation, clarity of budget targets and job relevant information on organizational performance. The object of this research is the Regional Apparatus Work Unit (SKPD) located in Seluma Regency. Tests in this study using quantitative methods. The analytical technique used in this research is the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The results of the study indicate that budgetary participation affects the clarity of budget targets, clarity of budget targets affects organizational performance, budgetary participation has an indirect effect on organizational performance with clarity of budget targets as a mediating variable, budgetary participation affects job relevant information, job relevant information influence on organizational performance, budgetary participation has an indirect effect on organizational performance with job relevant information as a mediating variable.